Environmental taxes and the effects of partial privatization on environmental R&D, environment and welfare. Issue 1 (31st December 2022) - Xing, Mingqing; Yang, Lin; Tan, Tingting; Wang, Xia; Li, Qingjun; Wang, Bo
Abstract: This paper considers environmental R&D (ER&D) of clean technology for reducing pollutant emissions in a polluting mixed duopoly and analyzes partial privatization's impacts on ER&D, environment and welfare. In the situation that environmental taxes are exogenously given, it finds that the impacts of privatization policy on ER&D and environment critically depend on the level of environmental damage. However, regardless of the marginal damage, an appropriate partial-privatization policy can increase social welfare. In addition, it also considers an endogenously determined optimal environmental tax and shows that if the marginal damage is high, partial privatization's impacts on ER&D, environment and social welfare may be not the same as the exogenous environmental tax situation.